2015
DOI: 10.1007/s11136-015-1032-5
|View full text |Cite
|
Sign up to set email alerts
|

Watchful waiting for subthreshold depression and anxiety in visually impaired older adults

Abstract: PurposeImmediate treatment of depression and anxiety may not always be necessary in resilient patients. This study aimed to determine remission rates of subthreshold depression and anxiety, incidence rates of major depressive and anxiety disorders, and predictors of these remission and incidence rates in visually impaired older adults after a three-month ‘watchful waiting’ period.MethodsA pretest–posttest study in 265 visually impaired older adults (mean age 74 years), from outpatient low-vision rehabilitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 45 publications
(50 reference statements)
1
24
0
Order By: Relevance
“…Gender and having a history of depressive, dysthymic or panic disorder was not a predictor for developing depressive or anxiety symptoms. However, a previous study in visually impaired older adults with subthreshold depression found that the female gender and psychiatric history was associated with the development of major depressive and anxiety disorders . Our results are probably biased because females and elderly with a psychiatric history, who are more vulnerable to develop depressive or anxiety symptoms, had already subthreshold depression or anxiety at baseline and were, therefore, excluded from this study in which we wanted to determine the incidence of these symptoms.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Gender and having a history of depressive, dysthymic or panic disorder was not a predictor for developing depressive or anxiety symptoms. However, a previous study in visually impaired older adults with subthreshold depression found that the female gender and psychiatric history was associated with the development of major depressive and anxiety disorders . Our results are probably biased because females and elderly with a psychiatric history, who are more vulnerable to develop depressive or anxiety symptoms, had already subthreshold depression or anxiety at baseline and were, therefore, excluded from this study in which we wanted to determine the incidence of these symptoms.…”
Section: Discussionmentioning
confidence: 71%
“…Depression and anxiety are well known transient conditions . A recent study in older adults with vision impairment and subthreshold depression and/or anxiety showed that after a three‐month watchful waiting period, in which no psychological treatment was offered, one‐third of the participants recovered from these symptoms and one‐fifth developed a depressive and/or anxiety disorder indicating that depression and anxiety symptoms fluctuate, which is similar to findings in the general population . Since interventions are usually only offered when symptoms manifest themselves, it is likely that no treatment is offered even though a person might be at high risk of developing clinically significant symptoms in the near future.…”
Section: Introductionmentioning
confidence: 62%
“…The implementation strategies mentioned above were used alone or in combination for managing specific MHP in the elderly population such as major depression, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] minor or sub-threshold depression, [39][40][41][42] depression and anxiety in residential care homes, [43][44][45][46][47] suicidal ideation, 48 alcohol abuse, 49,50 behavioural symptoms in Alzheimer, 51 and mental problems in specific patient groups. 15,[52][53][54][55][56] Evidence showed that the collaborative care strategy is best adapted for the organisation of MHCE, often combined with one of the other operational strategies (see Table 1). Studies on severe psychiatric disorders in the elderly were, however, sparse.…”
Section: Operational Strategiesmentioning
confidence: 99%
“…Five out of seven RCT studies suggested effective interventions to prevent and treat depression in AMD patients (53,55,57,59,61), and one of these studies also showed positive outcomes for anxiety (61). However, only 4 studies in our review had included an outcome measure for anxiety (60)(61)(62)(63), which suggests the need for additional research investigating the effect of psychological and psychosocial interventions on anxiety related to AMD.…”
Section: Discussionmentioning
confidence: 94%
“…The studies included in this review examined the effectiveness of psychosocial and psychological interventions which were mainly composed of cognitive-behavioural techniques such as self-management, self-help, problem solving, behavioural activation, and emotion-focused intervention. Although all studies have tested the effectiveness of the intervention programme to reduce symptoms of depression, only four studies included anxiety as an outcome measure (59)(60)(61)(62). Five out of seven RCT studies suggested effective interventions to prevent and treat depression in AMD patients (53,55,57,59,61), and one of these studies also showed positive outcomes for anxiety (61).…”
Section: Discussionmentioning
confidence: 99%